Character Education In Mathematics Learning Through Habits Of Mind Development To Support The Achievement Of Students’ Cognitive Mathematical Ability - Siregar, Hesty Marwani (Program Studi Pendidikan Matematika, Universitas Pancasakti Tegal, 2024)
Character education and learning mathematics are often considered as two different things. Whereas character education is one of the focuses of the Kurikulum Merdeka through the Profil Pelajar Pancasila, which can be instilled in all fields of study. One way to provide character education in mathematics learning is through inculcating habits of mind. This paper aims to find out whether character education through instilling habits of mind can support the achievement of students' mathematical cognitive abilities. The method used in writing this paper is literature study or literature review. From the results of the literature study, it is found that character education can be carried out by instilling habits of mind. This is because the habits of mind have 16 indicators which are positive characters. Besides being able to develop positive character, character education through inculcating habits of mind can also support the achievement of students' cognitive abilities, which can also be seen from several previous studies. This is due to the positive characters that have been embedded in students, for example, such as the characters of perseverance, curiosity, critical, analytical, communication, and empathy. This means that by providing character education through instilling habits of mind, not only positive character will be formed in students, but students' cognitive achievement will also be more optimal.